2016
DOI: 10.1161/circoutcomes.115.002491
|View full text |Cite
|
Sign up to set email alerts
|

Do Women With Anxiety or Depression Have Higher Rates of Myocardial Ischemia During Exercise Testing Than Men?

Abstract: W omen have been shown to have worse coronary artery disease (CAD) outcomes relative to men because more women (17%) than men (12%) die within 3 years of having their first myocardial infarction (MI), 1 and hospital mortality rates after an acute MI have been shown to be higher in women (16%) than in men (11%).2 Suggested reasons for this sex disparity include the unique presentation of CAD in women and delays associated with diagnosis and treatment onset among women relative to men.3-5 Sex differences are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
(50 reference statements)
1
18
0
1
Order By: Relevance
“…Nonetheless, we believe that post-MI anxiety should be taken into consideration in clinical practice, since it has been shown that not only depression but also pre-myocardial anxiety in the preceding 2 hours increase 10-year mortality rates in those aged > 65 years. 25 Moreover, Paine et al 26 recently published an article stating that women with anxiety and no CAD history had higher rates of ischemia than women without anxiety. Since women are more prone to anxiety, it is important to mention that many CAD symptoms (for example, fatigue, chest pain and shortness of breath) overlap with anxiety symptoms and might mask CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we believe that post-MI anxiety should be taken into consideration in clinical practice, since it has been shown that not only depression but also pre-myocardial anxiety in the preceding 2 hours increase 10-year mortality rates in those aged > 65 years. 25 Moreover, Paine et al 26 recently published an article stating that women with anxiety and no CAD history had higher rates of ischemia than women without anxiety. Since women are more prone to anxiety, it is important to mention that many CAD symptoms (for example, fatigue, chest pain and shortness of breath) overlap with anxiety symptoms and might mask CAD.…”
Section: Discussionmentioning
confidence: 99%
“…This is a sub-analysis of the Depression Effects on Coronary Artery Disease Events (DECADE) prospective observational Study, so the methods have been described elsewhere (Paine, Bacon, et al, 2016;Pelletier et al, 2015). Briefly, the sample included 2460 consecutive patients who presented to the Montreal Heart Institute (MHI) for diagnostic myocardial perfusion single photon emission computed tomography (SPECT) exercise stress testing between September 1998 and June 2002.…”
Section: Participantsmentioning
confidence: 99%
“…1,2 However, the mechanisms of these relationships are still a source of much debate. One of the strongest potential pathways linking acute psychological stress with worse outcomes is through mental stress-induced myocardial ischemia (MSIMI).…”
mentioning
confidence: 99%